Acrylate polymer

By developing an acrylic ester polymer with excellent high-temperature self-polymerization characteristics, the problems of insufficient heat resistance and residual glue pollution at high temperatures have been solved, and efficient heat resistance and low pollution are achieved.

CN119842003APending Publication Date: 2025-04-18NITTO DENKO SHANGHAI SONGJIANG +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311339038.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing acrylic adhesives are insufficient in heat resistance after high temperature use, and may cause residual glue contamination on the surface of the adhered.

Method used

An acrylate polymer has excellent self-polymerization characteristics under high temperature environments. By controlling the change rate of energy storage modulus in the range of 2 to 150, the high-temperature self-polymerization of the polymer is achieved, thereby improving heat resistance and reducing pollution.

Benefits of technology

It realizes excellent heat resistance of acrylate polymers in heat-resistant applications, while avoiding residual glue contamination on the adherend and having low pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004496838740000021
    Figure BDA0004496838740000021
  • Figure BDA0004496838740000022
    Figure BDA0004496838740000022
  • Figure BDA0004496838740000031
    Figure BDA0004496838740000031
Patent Text Reader

Abstract

The invention provides an acrylate polymer. The acrylate polymer has excellent high-temperature self-polymerization characteristic, when the acrylate polymer is applied to the heat-resistant adhesive tape, excellent heat resistance can be realized through the high-temperature self-polymerization characteristic of the acrylate polymer, residual adhesive pollution to an adhered object is avoided, and the acrylate polymer also has low pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an acrylate polymer, and in particular to an acrylate polymer having both excellent heat resistance and low pollution. Background Art

[0002] Generally, adhesives are in a soft solid (viscoelastic) state in a temperature range near room temperature and have the property of being easily bonded to an adherend by pressure. Taking advantage of this property, adhesives are widely used in various fields in the form of adhesive sheets with a substrate having an adhesive layer on a substrate or in the form of substrate-free adhesive sheets without a substrate.

[0003] Various properties are required of adhesives depending on the application. When used in heat-resistant applications such as heat-resistant protection or heat-resistant packaging processes, silicone polymers are usually used as adhesives. However, since the silicone polymers used significantly reduce the surface energy of the substrate, the wire bonding success rate will be reduced, affecting the performance of packaging yield, etc. Therefore, acrylic adhesives are currently being tried to replace silicone adhesives. However, when multiple high-temperature operations are required, acrylic adhesives are not resistant to high temperatures, and after high-temperature use, residual adhesive is easily contaminated on the surface of the adherend. Summary of the invention

[0004] Problem that the invention aims to solve

[0005] The present invention is made to solve the above-mentioned existing problems, and its purpose is to provide an acrylate polymer having excellent high-temperature self-polymerization properties. When the acrylate polymer is applied to a heat-resistant adhesive tape, the high-temperature self-polymerization properties of the acrylate polymer can achieve excellent heat resistance, and no residual adhesive pollution is generated on the adherend, and the acrylate polymer also has low pollution.

[0006] Solutions for solving problems

[0007] The present inventors conducted intensive research to solve the above-mentioned problems and found that when the polymer is used in a high-temperature environment, the secondary reaction causes the storage modulus of the polymer to continue to increase at high temperatures, thereby increasing the cohesive force, thereby solving the above-mentioned problems and completing the present invention.

[0008] That is, the present invention is as follows.

[0009] [1] An acrylic ester polymer, wherein the storage modulus change rate y calculated by the following formula (1) is 2 to 150, preferably 10 to 100,

[0010] y = A / B (1)

[0011] In formula (1), y represents the rate of change of storage modulus;

[0012] A represents the storage modulus of the acrylate polymer when heated at 200° C. for 2 h;

[0013] B represents the storage modulus of the acrylic ester polymer at 23°C.

[0014] [2] The acrylic ester polymer according to [1], wherein the acrylic ester polymer comprises, based on 100 parts by weight of all monomer components of the acrylic ester polymer, 70 to 90 parts by weight of a soft monomer, 5 to 15 parts by weight, preferably 5 to 10 parts by weight of a monomer represented by the following formula (a) or the following formula (b), and 5 to 12 parts by weight of a functional monomer,

[0015]

[0016] In formula (a), X1 represents -NH-R, wherein R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms;

[0017] A means that the terminal group contains a C=C side chain;

[0018]

[0019] In formula (b), X2 represents -NH;

[0020] A represents a side chain having one C=C at the terminal group.

[0021] [3] The acrylic acid ester polymer according to [2], wherein the acrylic acid ester polymer satisfies any one of the following conditions (i) to (iii):

[0022] (i) the soft monomer is a (meth)acrylate monomer represented by the following formula (c) having a glass transition temperature of -80 to -10°C,

[0023]

[0024] In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms,

[0025] Y represents a hydrogen atom or a methyl group;

[0026] (ii) the monomer represented by formula (a) comprises at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-hydroxymethylmethacrylamide and 2-[[(butylamino)-carbonyl]oxy]ethyl 2-acrylate,

[0027] The monomer represented by formula (b) comprises 2-acrylic acid-2-(2-oxo-1-imidazolinyl)ethyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)ethyl ester, 2-acrylic acid-2-(2-oxo-1-imidazolinyl)propyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)propyl ester, 2-acrylic acid-2-(2-oxo-1-imidazolinyl)butyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)butyl ester, N-[2- at least one of the group consisting of 2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide and 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide;

[0028] (iii) the functional monomer comprises a (meth)acrylate monomer containing a hydroxyl group and / or a (meth)acrylate monomer containing a carboxyl group,

[0029] The hydroxyl-containing (meth)acrylate monomer comprises at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate,

[0030] The carboxyl-containing (meth)acrylate monomer comprises at least one selected from the group consisting of (meth)acrylic acid, (iso)butylene acid, (cis / trans)-2-methyl-2-butenoic acid, isomethyl 2-butenoate, isoethyl 2-butenoate, isopropyl 2-butenoate, isobutyl 2-butenoate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 2-carboxybutyl (meth)acrylate and 2-carboxypentyl (meth)acrylate.

[0031] [4] The acrylic acid ester polymer according to any one of [1] to [3], wherein the acrylic acid ester polymer has a gel fraction of 10 to 50% when measured at 23°C after being heated at 150°C for 2 hours.

[0032] [5] The acrylic acid ester polymer according to any one of [1] to [3], wherein the thermal weight loss of the acrylic acid ester polymer when heated from 23°C to 200°C is 1% or less, preferably 0.6% or less.

[0033] [6] The acrylate polymer according to any one of [1] to [3], wherein the surface energy of the acrylate polymer is 20 to 35 mN / m.

[0034] [7] The acrylic acid ester polymer according to any one of [1] to [3], wherein the acrylic acid ester polymer has a glass transition temperature of -65 to -10°C, preferably -35 to -20°C.

[0035] [8] The acrylate polymer according to any one of [1] to [3], wherein the change rate of the 180° peel adhesion to the Cu plate (F A -F B ) / F A The absolute value of ×100 is 20% or less, preferably 10% or less,

[0036] Among them, F A The acrylate polymer is coated on a PI substrate, dried, and then laminated on a Cu plate, heated at 200°C for 1 hour, and then placed at 23°C × 50% RH for 0.5 hour to measure the adhesive strength.

[0037] F B The adhesive strength is measured after the acrylic acid ester polymer is coated on a PI substrate, dried, and bonded to a Cu plate, and then left at 23° C.×50% RH for 0.5 h.

[0038] [9] The acrylate polymer according to any one of [1] to [3], wherein the acrylate polymer has an ultraviolet absorption peak of 0.22 abs or less in the wavelength range of 250 to 300 nm.

[0039]

[10] . Use of the acrylate polymer according to any one of [1] to [9] for producing an adhesive.

[0040] Effects of the Invention

[0041] The acrylate polymer of the present invention has excellent high-temperature self-polymerization properties. When applied to a heat-resistant adhesive tape, the acrylate polymer can achieve excellent heat resistance through the high-temperature self-polymerization properties, and will not cause residual adhesive pollution to the adherend, and has low pollution. DETAILED DESCRIPTION

[0042] The following describes a suitable embodiment of the present invention. Matters necessary for implementing the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the field.

[0043] In the acrylic acid ester polymer of the present invention, the storage modulus change rate y calculated by the following formula (1) is 2 to 150, preferably 10 to 100.

[0044] y = A / B (1)

[0045] In formula (1), y represents the rate of change of storage modulus;

[0046] A represents the storage modulus of the acrylate polymer when heated at 200° C. for 2 h;

[0047] B represents the storage modulus of the acrylic ester polymer at 23°C.

[0048] In the present invention, by controlling the storage modulus change rate y calculated by formula (1) within the range of 2 to 150, the obtained acrylate polymer has excellent high-temperature self-polymerization properties. When it is applied to a heat-resistant adhesive tape, the high-temperature self-polymerization properties of the acrylate polymer can achieve excellent heat resistance, and will not cause residual adhesive contamination to the adherend, and also has low pollution, thereby achieving both excellent heat resistance and low pollution.

[0049] The storage modulus can be measured, for example, by the method described in Examples below.

[0050] In some specific embodiments, the storage modulus change rate y calculated by the above formula (1) is 2, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140 or 150.

[0051] Hereinafter, the acrylic acid ester polymer of the present invention will be described in detail.

[0052] In some preferred embodiments, based on 100 parts by weight of all monomer components of the acrylate polymer, the acrylate polymer comprises: 70 to 90 parts by weight of a soft monomer, 5 to 15 parts by weight, preferably 5 to 10 parts by weight of a monomer represented by the following formula (a) or by the following formula (b), and 5 to 12 parts by weight of a functional monomer.

[0053]

[0054] In formula (a), X1 represents -NH-R, wherein R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms;

[0055] A means that the terminal group contains a C=C side chain;

[0056]

[0057] In formula (b), X2 represents -NH;

[0058] A represents a side chain having one C=C at the terminal group.

[0059] In a preferred embodiment, the soft monomer comprises an alkyl (meth)acrylate. In the present specification, the term "alkyl (meth)acrylate" refers to an alkyl acrylate and / or an alkyl methacrylate.

[0060] As the alkyl (meth)acrylate, an alkyl (meth)acrylate having an alkyl group with 3 to 20 carbon atoms is preferred. Specific examples of the alkyl (meth)acrylate having an alkyl group with 3 to 20 carbon atoms are not particularly limited, and include propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2-EHA) are preferred. The (meth)acrylic acid alkyl esters may be used alone or in combination of two or more.

[0061] In some preferred embodiments, the soft monomer is preferably a (meth)acrylate monomer having a glass transition temperature of -80 to -10°C represented by the following formula (c):

[0062]

[0063] In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms,

[0064] Y represents a hydrogen atom or a methyl group.

[0065] Examples of the alkyl group having 3 to 20 carbon atoms represented by Z include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, 2-ethylhexyl, heptyl, octyl, isooctyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, or eicosyl.

[0066] Examples of the cycloalkyl group having 3 to 20 carbon atoms represented by Z include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclodecyl, cyclododecyl, 4-methylcyclohexyl, and 4-ethylcyclohexyl.

[0067] Examples of the (meth)acrylate monomer represented by formula (c) having a glass transition temperature of -80 to -10°C include 2-ethylhexyl acrylate (Tg: -70°C) and n-butyl acrylate (Tg: -55°C).

[0068] Based on 100 parts by weight of all monomer components of the acrylic ester polymer, the content of the soft monomer is preferably 70 to 90 parts by weight, more preferably 75 to 89 parts by weight. In some specific embodiments, based on 100 parts by weight of all monomer components of the acrylic ester polymer, the content of the soft monomer is preferably 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight or 90 parts by weight. When the content of the soft monomer is within the above range, excellent adhesion can be obtained.

[0069] In the monomer represented by formula (a), X1 represents -NH-R, wherein R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms.

[0070] Examples of the alkyl group having 1 to 6 carbon atoms represented by R include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, and hexyl.

[0071] Examples of the cycloalkyl group having 3 to 20 carbon atoms represented by R include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclodecyl, cyclododecyl, 4-methylcyclohexyl, and 4-ethylcyclohexyl.

[0072] The heteroatom in the heterocyclic group having 3 to 20 carbon atoms represented by the above R is preferably selected from N, O and / or S. In the present invention, the number of heteroatoms may be 1 or more. Examples of the heterocyclic group having 3 to 20 carbon atoms represented by the above R include: propiolactone group, lactam group, maleic anhydride group, tetrahydrofuranyl group, furanyl group, thienyl group, pyrrolyl group, thiazolyl group, pyridyl group, pyrimidyl group, quinolyl group, indolyl group, purinyl group, and the like.

[0073] In some preferred embodiments, the monomer represented by formula (a) is preferably a monomer represented by the following formula (a1),

[0074]

[0075] In formula (a1), Ra1 represents a hydrogen atom or a methyl group; Ra2 represents an alkyl group having 1 to 6 carbon atoms or -Ra4-Ra5; Ra3 represents an alkyl group having 1 to 6 carbon atoms or a hydrogen atom; Ra4 represents an alkyl group having 1 to 6 carbon atoms; Ra5 represents or a hydroxyl group; Ra6 represents an alkyl group having 1 to 6 carbon atoms; Ra7 represents an alkyl group having 1 to 6 carbon atoms.

[0076] Examples of the alkyl group having 1 to 6 carbon atoms represented by the above Ra2 to Ra4 and Ra6 to Ra7 include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl and hexyl.

[0077] In some preferred embodiments, the monomer represented by formula (a) is preferably a monomer represented by the following formula (a2),

[0078]

[0079] In formula (a2), Ra8 represents an alkylene group having 1 to 6 carbon atoms; Ra9 represents an alkyl group having 1 to 6 carbon atoms.

[0080] Examples of the alkylene group having 1 to 6 carbon atoms represented by Ra8 include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, a pentylene group, and a hexylene group.

[0081] Examples of the alkyl group having 1 to 6 carbon atoms represented by Ra9 include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, and hexyl.

[0082] In some preferred embodiments, the monomer represented by formula (a) comprises at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-hydroxymethylmethacrylamide and 2-[[(butylamino)-carbonyl]oxy]ethyl 2-acrylate.

[0083] The monomer represented by the above formula (b) is preferably selected from the group consisting of 2-(2-oxo-1-imidazolinyl)ethyl 2-acrylate, 2-(2-oxo-1-imidazolinyl)ethyl 2-methyl-2-acrylate, 2-(2-oxo-1-imidazolinyl)propyl 2-acrylate, 2-(2-oxo-1-imidazolinyl)propyl 2-methyl-2-acrylate, 2-(2-oxo-1-imidazolinyl)butyl 2-acrylate, 2-(2-oxo-1-imidazolinyl)butyl 2-methyl-2-acrylate, N-[ At least one of the group consisting of 2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide and 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide.

[0084] Based on 100 parts by weight of all monomer components of the acrylate polymer, the content of the monomer represented by formula (a) or represented by formula (b) is 5 to 15 parts by weight, more preferably 5 to 10 parts by weight. In some specific embodiments, based on 100 parts by weight of all monomer components of the acrylate polymer, the content of the monomer represented by formula (a) or represented by formula (b) is preferably 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight or 15 parts by weight. When the content of the monomer represented by formula (a) or represented by formula (b) is within the above range, the high temperature self-polymerization characteristics of the acrylate polymer can be improved, thereby obtaining excellent heat resistance.

[0085] As the functional monomer, a monomer having a polar group can be suitably used. The monomer having a polar group is useful for introducing a crosslinking point into the base polymer or increasing the cohesive force of the base polymer. The functional monomer can be used alone or in combination of two or more.

[0086] Specific non-limiting examples of the functional monomer include hydroxyl group-containing monomers and / or carboxyl group-containing monomers.

[0087] The content of the functional monomer is preferably 5 to 12 parts by mass, more preferably 6 to 11 parts by mass, based on 100 parts by mass of all monomer components of the acrylic ester polymer. When the content of the functional monomer is within the above range, the cohesive force of the adhesive can be prevented from becoming too high, and the adhesiveness can be improved.

[0088] A hydroxyl-containing monomer refers to a monomer having at least one hydroxyl group in the molecule. When the monomer component used to constitute the acrylic polymer includes a hydroxyl-containing monomer, that is, when the acrylic polymer includes a monomer unit derived from a hydroxyl-containing monomer, the cohesive force of the acrylic polymer is improved due to the formation of secondary bonds such as hydrogen bonds with the adherend, and the change in adhesive force over time can be more effectively suppressed. There is less residual adhesive on the adherend after peeling, and it has higher aggregation. The acrylic polymer of this embodiment can use one hydroxyl-containing monomer, or two or more hydroxyl-containing monomers.

[0089] As the hydroxyl group-containing monomer, a (meth)acrylate-based monomer containing a hydroxyl group is preferred.

[0090] Specific examples of hydroxyl-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.

[0091] There is no particular limitation on the content of the hydroxyl-containing monomer. For example, the content of the hydroxyl-containing monomer is 0.5 to 6 parts by mass, preferably 0.5 to 5 parts by mass, based on 100 parts by mass of all monomer components of the acrylic ester polymer. When the content of the hydroxyl-containing monomer is within the above range, the cohesive force of the acrylic ester polymer is improved due to the formation of secondary bonds such as hydrogen bonds with the adherend, which can more effectively suppress the change of the adhesive force over time, and there is less residual adhesive on the adherend after peeling, and the acrylic ester polymer has higher aggregation.

[0092] A carboxyl group-containing monomer refers to a monomer having at least one carboxyl group in the molecule. When the raw material monomer of the acrylic ester polymer includes a carboxyl group-containing monomer, the cohesive force of the acrylic ester polymer is improved due to the formation of secondary bonds such as hydrogen bonds with the adherend, and the change in adhesive force over time can be more effectively suppressed. Moreover, less residual adhesive is left on the adherend after peeling, and the acrylic ester polymer has higher aggregation.

[0093] As the carboxyl group-containing monomer, a (meth)acrylate monomer containing a carboxyl group is preferred.

[0094] As specific examples of carboxyl-containing monomers, for example, (methyl) acrylic acid, (iso) butylene acid, (cis / trans)-2-methyl-2-butylene acid, 2-butylene acid isomethyl ester, 2-butylene acid isoethyl ester, 2-butylene acid isopropyl ester, 2-butylene acid isobutyl ester, (methyl) acrylic acid-2-carboxyethyl ester, (methyl) acrylic acid-2-carboxypropyl ester, (methyl) acrylic acid-2-carboxybutyl ester and (methyl) acrylic acid-2-carboxypentyl ester can be used alone. Any one of the above carboxyl-containing monomers can be used alone or in combination of two or more.

[0095] The content of the carboxyl group-containing monomer is not particularly limited, for example, based on 100 parts by mass of all monomer components of the acrylic ester polymer, the content of the carboxyl group-containing monomer is preferably 1 to 10 parts by mass. When the content of the carboxyl group-containing monomer is within the above range, the cohesive force of the acrylic ester polymer is improved due to the formation of secondary bonds such as hydrogen bonds with the adherend, which can more effectively suppress the change of the adhesive force over time, and there is less residual adhesive on the adherend after peeling, and the acrylic ester polymer has higher aggregation.

[0096] The method for obtaining the acrylic ester polymer is not particularly limited, and various known polymerization methods such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization can be appropriately used. For example, solution polymerization can be preferably used. As a monomer supply method for solution polymerization, a batch feeding method of supplying all monomer raw materials at one time, a continuous supply (drip) method, a divided supply (drip) method, etc. can be appropriately used. The polymerization temperature during solution polymerization can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be set to, for example, about 20 to 170°C (typically about 40 to 140°C).

[0097] The solvent (polymerization solvent) used in solution polymerization can be appropriately selected from existing known organic solvents. For example, any one solvent or a mixed solvent of two or more selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropanol (e.g. monohydric alcohols with 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone, etc. can be used.

[0098] The initiator used in the polymerization can be appropriately selected from the existing known polymerization initiators according to the type of polymerization method. For example, one or more of the azo polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN) can be preferably used. As other examples of polymerization initiators, there can be listed: persulfates such as potassium persulfate; peroxide initiators such as benzoyl peroxide and hydrogen peroxide; substituted ethane initiators such as phenyl substituted ethane; aromatic carbonyl compounds, etc. As other examples of polymerization initiators, redox initiators obtained by combining peroxides and reducing agents can be listed. Such polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used is the usual amount, for example, it can be selected from the range of about 0.005 mass parts to about 1 mass part (typically about 0.01 mass parts to about 1 mass part) relative to 100 mass parts of all monomer components.

[0099] The weight average molecular weight (Mw) of the acrylic acid ester polymer in the technology disclosed herein is not particularly limited, and may be, for example, 1,000,000 or less, preferably 400,000 or more. Generally, when the weight average molecular weight Mw exceeds 1,000,000, the cohesive force increases due to the effect of polymer entanglement, thereby reducing the fluidity, and sometimes a sufficient bonding area cannot be obtained, and the adherend cannot be fixed.

[0100] Here, the weight average molecular weight (Mw) refers to a value converted to standard polystyrene obtained by gel permeation chromatography (GPC). For example, a GPC apparatus can be used with the model name "HLC-8320GPC" (column: TSKgelGMH-H(S), manufactured by Tosoh Corporation).

[0101] In a preferred embodiment, the gel fraction of the acrylic ester polymer measured at 23° C. after being heated at 150° C. for 2 hours is 10 to 50%. When the gel fraction is within the above range, excellent adhesive properties can be obtained. The gel fraction can be adjusted, for example, by selecting the composition and molecular weight of the acrylic ester polymer.

[0102] The gel fraction can be measured by, for example, the method described in Examples below.

[0103] In some preferred embodiments, the thermal weight loss of the acrylic polymer when heated from 23°C to 200°C at a heating rate of 10°C / min is 1% or less, preferably 0.6% or less. When the thermal weight loss rate of the acrylic polymer is within the above range, an acrylic polymer with better heat resistance can be provided. When the acrylic polymer is used in a heat-resistant protection process, it will not be significantly increased or decreased due to thermal degradation, or the cohesive force will not be reduced.

[0104] The thermal weight loss can be measured, for example, by the method described in Examples below.

[0105] In some preferred embodiments, the surface energy of the acrylate polymer is 20 to 35 mN / m. When the surface energy of the acrylate polymer is within the above range, a low-staining acrylate polymer can be provided.

[0106] The surface energy can be measured, for example, by the method described in the Examples described below.

[0107] In some preferred embodiments, the glass transition temperature (Tg) of the acrylate polymer is preferably -65 to -10°C, more preferably -35 to -20°C.

[0108] Here, the Tg of the acrylic ester polymer refers to the Tg obtained by the Fox equation based on the composition of the monomer components used in the synthesis of the polymer. The Fox equation is shown below and is a relationship between the Tg of the copolymer and the glass transition temperature Tgi of the homopolymer obtained by homopolymerizing the monomers constituting the copolymer.

[0109] 1 / Tg=Σ(W i / Tg i )

[0110] In the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), W i represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), Tg i represents the glass transition temperature of the homopolymer of monomer i (unit: K).

[0111] As the glass transition temperature of the homopolymer, the value described in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. For monomers for which multiple values ​​are described in this document, the highest value is adopted. In the case where it is not described in the above-mentioned Polymer Handbook, the value obtained by the measurement method described in Japanese Patent Publication No. 2007-51271 is used.

[0112] In some preferred embodiments, the change rate of the 180° peel adhesion of the acrylate polymer to the Cu plate (F A -F B ) / F A The absolute value of ×100 is 20% or less, preferably 10% or less,

[0113] Among them, F AThe acrylate polymer is coated on a PI substrate, dried, and then laminated to a Cu plate, heated at 200°C for 1 hour, and then placed at 23°C × 50% RH for 0.5 hour to measure the adhesive strength.

[0114] F B The acrylate polymer was coated on a PI substrate, dried, and then bonded to a Cu plate, and then left at 23°C x 50% RH for 0.5 h and measured for adhesive strength.

[0115] When the change rate of 180° peel adhesion of acrylate polymer to Cu plate (F A -F B ) / F A When the absolute value of ×100 is within the above range, it can provide excellent adhesion performance and excellent peeling operability, can give full play to the adhesive effect required during use, achieve excellent adhesion, and can be easily peeled off after use without causing damage to the adherend or causing residual adhesive pollution.

[0116] The adhesive force can be measured, for example, by the method described in Examples below.

[0117] In some preferred embodiments, the acrylate polymer has an ultraviolet absorption peak of less than 0.22 abs in the wavelength region of 250 to 300 nm. When the ultraviolet absorption peak in the wavelength region of 250 to 300 nm is within the above range, the monomer side groups represented by formula (a) or by formula (b) form crosslinking groups with the functional monomer side groups.

[0118] The ultraviolet absorption peak in the wavelength region of 250 to 300 nm can be measured, for example, by the method described in the Examples described below.

[0119] (use)

[0120] The acrylate polymer disclosed herein can be used, for example, in the production of adhesives, etc. In particular, when the acrylate polymer of the present invention is used in the production of adhesives, it can provide excellent heat resistance.

[0121] Example

[0122] The present invention is specifically described below by way of examples, but the present invention is not limited to these examples. The evaluation methods in the examples are as follows. In addition, in the examples, unless otherwise specified, "parts" and "%" are weight references. If no specific conditions are specified in the examples, the conditions are carried out under conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the materials or instruments used are conventional products that can be obtained commercially.

[0123] <Preparation of Acrylate Polymer>

[0124] Example 1

[0125] Into a reaction container equipped with a stirrer, a thermometer, a nitrogen inlet tube and a reflux condenser, 89 parts of 2-ethylhexyl acrylate (2-EHA), 2 parts of 2-hydroxyethyl acrylate (HEA), 4 parts of acrylic acid (AA), 5 parts of ethylene urea ethoxy methacrylate (WAMX), and 200 parts of ethyl acetate as a polymerization solvent were added, and after stirring at 65° C. for 1.5 hours under a nitrogen atmosphere, 0.3 parts of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and the reaction was carried out at 65° C. for 4 to 5 hours to obtain a solution of acrylate polymer A1.

[0126] Embodiments 2 to 7

[0127] Acrylate polymers A2 to A7 were prepared in the same manner as in the acrylic acid ester polymer A1 except that the types and amounts of the monomer components were changed as shown in Table 1.

[0128] Comparative Examples 1 to 4

[0129] Acrylate polymers C1 to C4 were prepared in the same manner as in the acrylic acid ester polymer A1 except that the types and amounts of the monomer components were changed as shown in Table 2.

[0130] Table 1

[0131]

[0132] Table 2

[0133]

[0134] <Preparation of Adhesive Sheet>

[0135] Example 8

[0136] To the solution of the acrylic polymer A1 prepared in Example 1, 10 parts of ethyl acetate was added based on 100 parts of the acrylic polymer A1 contained in the solution, and the mixture was uniformly mixed to prepare a pressure-sensitive adhesive composition B1.

[0137] The adhesive composition B1 was applied on one side of a PI film having a thickness of 25 μm as a substrate layer, and then heated at 120° C. for 3 minutes to form an adhesive layer having a thickness of 8 μm, and then a PET release film was attached to the adhesive layer.

[0138] The evaluation results are shown in Table 3.

[0139] Example 9

[0140] To the solution of the acrylic ester polymer A2 prepared in Example 2, 10 parts of ethyl acetate was added based on 100 parts of the acrylic ester polymer A2 contained in the solution, and the mixture was uniformly mixed to prepare a pressure-sensitive adhesive composition B2.

[0141] The adhesive composition B2 was applied to one side of a PI film having a thickness of 25 μm as a substrate layer, and then heated at 120° C. for 3 minutes to form an adhesive layer having a thickness of 8 μm. Thus, an adhesive sheet was obtained. The evaluation results are shown in Table 3.

[0142] Embodiments 10 to 14

[0143] A pressure-sensitive adhesive sheet was obtained in the same manner as in Example 9 except that the type of the acrylic acid ester polymer was changed as shown in Table 3. The evaluation results are shown in Table 3.

[0144] Comparative Examples 5 to 8

[0145] A pressure-sensitive adhesive sheet was obtained in the same manner as in Example 9 except that the type of the acrylic acid ester polymer was changed as shown in Table 4. The evaluation results are shown in Table 4.

[0146] Table 3

[0147]

[0148] Table 4

[0149]

[0150] <Evaluation Test>

[0151] (1) Storage modulus change rate

[0152] Testing instrument: Waters Technology Co., Ltd., rheometer model: ARES G2;

[0153] Test conditions: angular frequency fixed at 6.28 rad / s, constant temperature maintained at 250°C for 2h, oscillation strain 4.98%; specifically, the acrylate polymers of the embodiments and comparative examples were used to prepare adhesive layers (thickness: 50 μm) for measurement. Then, the adhesive layer was punched into a diameter of 7.9 mm and fixed in the form of being clamped by parallel plates, and the sample obtained was used as the measurement specimen. For the above-mentioned measurement specimen, a measurement device (manufactured by Waters Technologies, Inc., rheometer model: ARESG2) was used to measure the storage modulus when heated at 23°C and 200°C for 2h under the above-mentioned conditions. The results are shown in Tables 1 to 2.

[0154] (2) Gel rate

[0155] Heat the naturally dried acrylic polymer in an oven at 150°C for 2 hours, take (0.5-1.0g) of a sample weighing m1 and put it into a 50mL glass bottle, and soak it in toluene for 1 week. After filtering the soaking mixture with filter paper (product name: NTF-1122), the remaining residue is dried at 120°C and weighed m2.

[0156] Gel fraction = (m1-m2) / m1*100%

[0157] (3) Thermal weight loss

[0158] Testing instrument: Waters Technology Co., Ltd., thermogravimetric analyzer model: TGA550;

[0159] Test conditions: nitrogen protection, temperature rise from 23℃ to 200℃, ramp 10℃ / min, test thermal weight loss at 200℃. Ramp 10℃ / min; constant temperature 240.0min; mass flow rate 200mL / min.

[0160] (4) Surface energy

[0161] The test fluid was distilled water.

[0162] Test instrument: KRUSS, contact angle analyzer model DSA100

[0163] Specifically, the acrylic polymer was evenly coated on the SUS403BA plate with a coating thickness of 8 μm and dried at 120° C. for 3 min. In a test environment of 23° C. and 50% RH, the test sample plate prepared above was placed on the test platform of the contact angle analyzer, and the test liquid was dropped on the polymer surface to test the surface energy.

[0164] (5) Glass transition temperature

[0165] Test instrument: Manufacturer: PerkinElmer, Differential Scanning Calorimeter Model: DSC8000

[0166] Specifically, the acrylic ester polymer was dried naturally, and about 0.1 g of the polymer was put into a DSC test pan to test the glass transition temperature. Test conditions: nitrogen protection, heating from -70°C to 200°C, with a heating ramp of 10°C / min.

[0167] (6) Adhesion F A

[0168] The pressure-sensitive adhesive sheets prepared in the respective Examples and Comparative Examples were used as test pieces.

[0169] Under a standard environment of 23°C and 50% RH, the release liner covering the adhesive surface of each test piece was peeled off, and the exposed adhesive surface was pressed against an adherend (Cu plate) by reciprocating a 2 kg roller once, and then heated in an oven at 200°C for 1 hour. The test piece pressed against the adherend in this manner was left under the above standard environment for 30 minutes, and then peeled at a tensile speed of 300 mm / min and a peeling angle of 180° using a tensile tester (manufactured by Shimadzu Corporation, product name "Tensilon") according to JIS Z 0237, and the force required for the peeling (180° peeling adhesive force) (N / 20 mm) was measured.

[0170] (7) Adhesion F B

[0171] The pressure-sensitive adhesive sheets prepared in the respective Examples and Comparative Examples were used as test pieces.

[0172] Under the standard environment of 23°C and 50%RH, the release liner covering the adhesive surface of each test piece was peeled off, and a 2 kg roller was reciprocated once to press the exposed adhesive surface onto the adherend (Cu plate). After the test piece pressed onto the adherend by the operation was placed under the standard environment for 30 minutes, it was peeled off at a tension speed of 300 mm / min and a peeling angle of 180° using a tensile testing machine (manufactured by Shimadzu Corporation, product name "Tensilon") according to JIS Z0237, and the force required for the peeling (180° peeling adhesive force) (N / 20mm) was measured.

[0173] (7) UV absorption peak point

[0174] Sample treatment: 1g of acrylate polymer was soaked in 30mL of alcohol for 36h, and the mixture of alcohol and extract was tested by UV.

[0175] Test instrument: UV-visible spectrophotometer, model U-3900, manufacturer HITACHI

[0176] Measurement type: Wavelength scan

[0177] Data Mode: Abs

[0178] Starting wavelength: 800.00nm

[0179] End wavelength: 190.00nm

[0180] Scanning speed: 300 nm / min

[0181] Sampling interval: 1.00nm

[0182] (8) Pollution

[0183] The pressure-sensitive adhesive sheets prepared in the respective Examples and Comparative Examples were used as test pieces.

[0184] Under the standard environment of 23°C and 50%RH, the peeling liner covering the adhesive surface of each test piece was peeled off, and the exposed adhesive surface was pressed to the adherend C26000 copper plate by a 2kg roller back and forth once, and then placed in a 200°C oven for heating for 1h. After the test piece pressed to the adherend by such operation was placed under the above standard environment for 30 minutes, it was peeled off according to JIS Z 0237 using a tensile testing machine (manufactured by Shimadzu Corporation, product name "Tensilon") at a tensile speed of 300mm / min and a peeling angle of 180°, and the residual adhesive on the adhered object was observed. Evaluation was performed according to the following criteria.

[0185] ○: No residual glue

[0186] △: The residual adhesive area is greater than 0 and less than 10%

[0187] ×: The residual adhesive area is more than 10%

[0188] (9) High temperature warpage

[0189] The pressure-sensitive adhesive sheets prepared in the respective Examples and Comparative Examples were used as test pieces.

[0190] Under the standard environment of 23℃ and 50%RH, peel off the release liner covering the adhesive surface of each test piece and stick it flat on the top of the A-shaped copper column (C26000 copper column, top angle 120°). Heat the copper to 260℃ and maintain for 3 minutes, and visually observe the warping of the adhesive sheet. Evaluate according to the following criteria.

[0191] ○: No warping

[0192] △: Warping area is greater than 0 and less than 10%

[0193] ×: Warping area is 10% or more

[0194] (10) Fixed load

[0195] A commercially available double-sided adhesive tape was pasted on one side of a C26000 copper plate cleaned with toluene as an adherend. One of the adhesive sheets was pasted on the side of the double-sided adhesive tape opposite to the copper plate. Another adhesive sheet was cut and the adhesive layers of the two adhesive sheets were aligned and pasted on one side, with a pasting area of ​​20 mm x 100 mm. A 400 g weight was hung on one side of the other adhesive sheet and placed at 23°C x 50 RH% for 24 hours, and the separation amount of the aligned pasted area was measured.

[0196] ◎: The separation of the aligned pasting area is less than 40 mm

[0197] ○: The separation amount of the aligned pasting area is 40 to 80 mm

[0198] ×: The separation of the aligned and pasted area is greater than 80 mm

[0199] (11) Comprehensive evaluation

[0200] Based on the above evaluation results, a comprehensive evaluation was performed according to the following criteria.

[0201] ○: All evaluation items are "○"

[0202] △: There is no "×" in the evaluation items, but there is at least one "△"

[0203] ×: There are 1 or more "×" in the evaluation items

[0204] As can be seen from Table 1 and Table 3, the adhesive sheets prepared from the acrylic ester polymers of Examples 1 to 7 have excellent high temperature warpage evaluation results, excellent high temperature resistance, and no residual adhesive contamination to the adherend, and also have low pollution.

[0205] It can be seen from Table 2 and Table 4 that the adhesive sheets prepared from the acrylic ester polymers of Comparative Examples 1 to 4 have poor high-temperature warpage evaluation results, cannot meet the high-temperature heat resistance requirements, and also produce residual adhesive pollution.

[0206] Industrial Applicability

[0207] The acrylate polymer of the present invention has excellent high-temperature self-polymerization properties. When applied to a heat-resistant adhesive tape, the acrylate polymer can achieve excellent heat resistance through the high-temperature self-polymerization properties, and will not cause residual adhesive pollution to the adherend, and has low pollution.

Claims

1. An acrylate polymer, characterized in that The storage modulus change rate y calculated by the following formula (1) is 2 to 150, preferably 10 to 100. y = A / B (1) In formula (1), y represents the rate of change of storage modulus; A represents the storage modulus of the acrylate polymer when heated at 200° C. for 2 h; B represents the storage modulus of the acrylic ester polymer at 23°C.

2. The acrylate polymer according to claim 1, characterized in that Based on 100 parts by weight of all monomer components of the acrylic ester polymer, the acrylic ester polymer comprises: 70 to 90 parts by weight of a soft monomer, 5 to 15 parts by weight, preferably 5 to 10 parts by weight of a monomer represented by the following formula (a) or the following formula (b), and 5 to 12 parts by weight of a functional monomer. In formula (a), X1 represents -NH-R, wherein R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms; A means that the terminal group contains a C=C side chain; In formula (b), X2 represents -NH; A represents a side chain having one C=C at the terminal group.

3. The acrylate polymer according to claim 2, characterized in that The acrylic acid ester polymer satisfies any one of the following conditions (i) to (iii): (i) the soft monomer is a (meth)acrylate monomer represented by the following formula (c) having a glass transition temperature of -80 to -10°C, In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms, Y represents a hydrogen atom or a methyl group; (ii) the monomer represented by formula (a) comprises at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-hydroxymethylmethacrylamide and 2-[[(butylamino)-carbonyl]oxy]ethyl 2-acrylate, The monomer represented by formula (b) comprises 2-acrylic acid-2-(2-oxo-1-imidazolinyl)ethyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)ethyl ester, 2-acrylic acid-2-(2-oxo-1-imidazolinyl)propyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)propyl ester, 2-acrylic acid-2-(2-oxo-1-imidazolinyl)butyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)butyl ester, N-[2- at least one of the group consisting of 2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide and 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide; (iii) the functional monomer comprises a (meth)acrylate monomer containing a hydroxyl group and / or a (meth)acrylate monomer containing a carboxyl group, The hydroxyl-containing (meth)acrylate monomer comprises at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate, The carboxyl-containing (meth)acrylate monomer comprises at least one selected from the group consisting of (meth)acrylic acid, (iso)butylene acid, (cis / trans)-2-methyl-2-butenoic acid, isomethyl 2-butenoate, isoethyl 2-butenoate, isopropyl 2-butenoate, isobutyl 2-butenoate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 2-carboxybutyl (meth)acrylate and 2-carboxypentyl (meth)acrylate.

4. The acrylate polymer according to any one of claims 1 to 3, characterized in that The gel fraction of the acrylic ester polymer measured at 23° C. after being heated at 150° C. for 2 hours is 10 to 50%.

5. The acrylate polymer according to any one of claims 1 to 3, characterized in that The thermal weight loss of the acrylic acid ester polymer when the temperature is increased from 23° C. to 200° C. is 1% or less, preferably 0.6% or less.

6. The acrylate polymer according to any one of claims 1 to 3, characterized in that The surface energy of the acrylic ester polymer is 20 to 35 mN / m.

7. The acrylate polymer according to any one of claims 1 to 3, characterized in that The glass transition temperature of the acrylic ester polymer is -65 to -10°C, preferably -35 to -20°C.

8. The acrylate polymer according to any one of claims 1 to 3, characterized in that The change rate of its 180° peeling adhesion to Cu plate (F A -F B ) / F A The absolute value of ×100 is 20% or less, preferably 10% or less, Among them, F A The acrylate polymer is coated on a PI substrate, dried, and then laminated on a Cu plate, heated at 200°C for 1 hour, and then placed at 23°C × 50% RH for 0.5 hour to measure the adhesive strength. F B The adhesive strength is measured after the acrylic acid ester polymer is coated on a PI substrate, dried, and bonded to a Cu plate, and then left at 23° C.×50% RH for 0.5 h.

9. The acrylate polymer according to any one of claims 1 to 3, characterized in that The ultraviolet absorption peak of the acrylic ester polymer in the wavelength region of 250 to 300 nm is less than 0.22 abs.

10. Use of the acrylate polymer according to any one of claims 1 to 9 in the manufacture of an adhesive.

Citation Information

Patent Citations

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A